AB0453 The Quality of Life of The Kyrgyz Cohort of Patients with SLE According To The Prospective Study. (15th July 2016) - Koilubaeva, G.; Aseeva, E.; Soloviev, S.; Nasonov, E.; Reshetnyak, T.; Djumagulova, A.; Eralieva, V.; Karimova, E.
Abstract : Background: Systemic lupus erythematosus (SLE) is a devastating disease affecting different organs, ultimately leading to organ failure and death. To date, there are no data regarding the real-life picture of SLE in Kyrgyzstan. Objectives: The goal of the study is evaluation of the quality of life among Kyrgyz cohort of patients with SLE according to the prospective study. Methods: 60 patients with definite diagnosis of SLE (ACR, 1997; SLICC, 2012) were treated in the department of rheumatology of NCCIM and observed from 2012 to 2015. They were evaluated by sex, age, disease duration, activity of SLE according the SLEDAI-2K, irreversible organ damage by SLICC Damage Index (SDI), quality of life using the SF-36 questionnaire, LupusQoL, HADS, FACIT, therapy, with monitoring of all parameters every six months for 2 years. From the data of the immunological studies immune linear (immunoblot) "ANA-LIA-Max 17" were analyzed with a purpose of detecting the antibodies of double-stranded DNA, Sm D1 antigen and antibodies of double-stranded DNA-linked immunosorbent analyisis (ELISA), C3-C4 components complement, indirect immunofluorescence of the antinuclear antibody cells of line Hep-2. Results: Patients were mainly from the northern region of the republic (81.7%). The vast majority were women (86.7%), with average age 30 years old, with disease duration of about 1.0 years. Dates of illness onset to verify the diagnosis ranged from 1 month to 9 years. The clinical course dominated patients with acute one (47%) and high activity (57%). The clinical symptoms of were cutaneous and articular syndrome (84.2% and 72.3%, respectively), the defeat of the serous membranes (88%) and kidney (68%). Before the treatment, according to the overall SF-36 questionnaire all SLE patients had lower QOL revealed. Marked limitation of life activity of patients was due to the presence of physical and emotional problems with severe anxiety and depression affects on their social functioning. After 2 years significant improvement in quality of life on many scales, except for the scale of mental health is noted. Attention is drawn to the deterioration of quality of life on the scale of "viability", which characterizes the patient a sense of lack of strength and energy for the period of the disease. The lowest quality of life is reported among Kyrgyz patients in the comparative analysis to QOL of patients with SLE in other 3 countries of Europe (UK, France and Italy) and Russia. Despite the reduction of disease activity (p<0, 001) among Kyrgyz cohort of patients the baseline QOL of Russian SLE patients for a period of two years of careful clinical supervision was not achieved. Conclusions: The low quality of life among Kyrgyz cohort of patients with SLE is associated with poor physical, emotional and social functioning. Despite the reduction of disease activity during the treatment, quality of life on the scale of "viability, lack of improvement of mental health component is identified as declining". Disclosure of Interest: None declared